Presence of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae in bulk-tank milk of bovine dairy farms in Antioquia, Colombia - Vásquez-Jaramillo, Laura; Ramírez, Nicolás F.; Akineden, Ömer; Fernández Silva, Jorge A. (Revista Colombiana de Ciencias Pecuarias, 2017)
<!-- [if gte mso 9]> 0 0 1 916 5044 Universidad de Antioquia 42 11 5949 14.0 96 <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES-CO JA X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--><!--StartFragment--> Background: antibiotic resistance is spreading worldwide. It is important to evaluate whether foods of animal origin constitute a reservoir of resistance genes. Objective: the aim of the present study was to assess the occurrence and characterize extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae from bulk-tank milk samples of dairy farms located in Entrerríos, Antioquia (Colombia). Methods: a total of 120 randomly selected raw milk samples (one bulk-tank milk sample per dairy farm) were collected between September and October, 2013. A commercial chromogenic agar was used for screening presumptive ESBL-E. Identification of genus and species of isolates was performed with a commercial biochemical identification kit. The ESBL production was confirmed using the double disc synergy test. An antimicrobial susceptibility test was performed by the agar disc diffusion method and the automatized broth microdilution method. The ESBL-positive isolates were analyzed for the presence of bla genes by polymerase chain reaction (PCR) and sequencing. For the exploration of risk factors, information on dairy farm management practices was recorded using a questionnaire and the associations of predictors and results were tested with a logistic regression analysis. Results: the ESBL-E were isolated from 3.3% (4/120; CI 95%: 3-3.5%) of the samples. Farm size was the only factor associated with the presence of ESBL-E (OR = 11.5; CI 95%: 1.14-115.54; p = 0.038). All isolates were resistant to several antibiotics and harbored blaCTX-M-96 (alternate name CTX-M-12a) enzymes. Conclusion: although apparent frequency of ESBL-E was low, the presence of these resistant bacteria in milk may constitute a public health risk and should be further investigated. . Resumo Palavras chave: CTX-M-12A, gado, leite crua, resistência aos antibióticos, saúde pública. <!--EndFragment-->